THE IMPORTANCE OF CONCENTRATION IN ELEMENTARY SCHOOL STUDENTS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article provides methods and recommendations for focusing the attention of elementary school students